Complex Crystal Structure Determination and in vitro Anti–non–small Cell Lung Cancer Activity of Hsp90N Inhibitor SNX-2112 - Zhao, Dong; Xu, Yi-Ming; Cao, Lu-Qi; Yu, Feng; Zhou, Huan; Qin, Wei; Li, Hui-Jin; He, Chun-Xia; Xing, Lu; Zhou, Xin; Li, Peng-Quan; Jin, Xin; et al. (Frontiers in Cell and Developmental Biology, 2021)
SNX-2112 as a promising anti-cancer lead compound targeting to heat shock protein 90 (Hsp90), absence of complex crystal structure of Hsp90N-SNX-2112 hampered further structural optimization and understanding on molecular interaction mechanism. Herein, a high-resolution complex crystal structure of Hsp90N-SNX-2112 was successfully determined by X-ray diffraction (XRD, resolution limit, 2.10 Å, PDB ID 6LTK) and their molecular interaction was analyzed in detail, which suggested that SNX-2112 perfectly installed in the ATP-binding pocket to disable molecular chaperone activity of Hsp90, therefore exhibitedfavorable inhibiting activity on three non-small-cell lung cancer (NSCLC) cell lines (IC50, 0.50±0.01 μM for A549, 1.14±1.11 μM for H1299, 2.36±0.82 μM for H1975) by inhibited proliferation, induced cell cycle arrest and promoted apoptosis. SNX-2112 exhibited an intense binding force with its target Hsp90N and favorable thermodynamic process with the target Hsp90N verified by thermal shift assay (TSA, ΔTm, -9.51±1.00°C) and isothermal titration calorimetry (ITC, Kd, 14.10±1.60 nM). Based on the complex crystal structure and molecular interaction analysis, thirty-two novel SNX-2112 derivatives were designed and twenty-five new ones displayed increased binding force with the target Hsp90N verified by molecular docking evaluation. The results would provide new ideas and guides for anti-NSCLC new drug development based on the lead compound SNX-2112.